PENGARUH ZEOLIT DAN KOMPOS TERHADAP RETENSI AIR, KAPASITAS TUKAR KATION, DAN PERTUMBUHAN TANAMAN SORGUM (Sorghum bicolor (L.) Moench) PADA ULTISOL - Sayyida Camilla Balqies; Sugeng Prijono; I Made Sudiana (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Ultisol is one of soils type in Indonesia which has several problemsr for the cultivation of plants such as low pH, high Al saturation, low content of organic matter, and limited water storage. The objective of this study was to investigate the effect of zeolite and compost application on water retention, cation exchange capacity, and growth of sorghum at an Ultisol. The study was conducted using a completely randomized factorial design with two factors, the first factor was zeolite doses with five levels consisting of Z0 (no zeolite), Z1 (20 t ha-1), Z2 (40 t ha-1), Z3 60 t ha-1), Z4 (80 t ha-1) and the second factor is variation of compost dosage with three levels consisting of K0 (no compost), K1 (compost 3%), K2 (compost 6%) Each treatment was repeated three times. The results showed that in the treatment of zeolite 80 t ha-1 water retention increased by 13,7% and in the treatment of compost 6% reached 13,76% but there was no interaction between zeolite and compost to water retention. The increase of water retention was due to the increase in C-organic and porosity and the decrease of soil bulk density. The application of zeolite and compost succeeded in increasing the cation exchange capacity at the zeolite treatment of 80 t ha-1 + 6% compost to 17,46 cmol kg-1 due to the increase of soil pH. If zeolite and compost were given in high doses they could increase the growth of sorghum.